Usability evaluation of chilean academic public library web sites using the SIRIUS method - Saldías Kiefer, Leslie (2021)
This article presents the results of a heuristic usability evaluation applied to 17 websites of libraries of public chilean universities, using the SIRIUS method ”System of Web Usability Evaluation, User Oriented and Based on the Determination of Critical Tasks”  For data collection, SIRIUS fixed guideline was used, which contains 10 heuristics that are subdivided into a total of 83 sub-heuristics evaluated by 5 experts with knowledge about libraries and usability websites. The results indicate that the best evaluated university libraries have good labeling mechanisms, layout and ease of interaction, while, as a whole, the websites lack navigation aids for their users. Finally, it is concluded that heuristic evaluation is a valid, fast, easy and applicable method in university library websites, as long as experts and heuristics are properly defined. Likewise, SIRIUS is an adequate tool since it has a fixed guideline that allows evaluations to be obtained quickly and to facilitate the comparison of its results.